Description of intraoral pressures on sub-palatal space in young adult patients with normal occlusion - Fuentes, Ramón (Int J Clin Exp Med, 2015)
Under normal conditions, the oral cavity presents a perfect system of equilibrium between teeth, soft tissues and tongue. The equilibrium of soft tissues forms a closed capsular matrix, generating differences with the atmospheric environment. This difference is known as intraoral pressure. Negative intraoral pressure is fundamental to the stabilization of the soft palate and tongue, reducing neuromuscular activity for the permeability of the respiratory tract. Thus, the aim of this study was to describe the variations of intraoral pressure of the sub-palatal space (SPS) under different physiological conditions and biofunctional phases. A case series was conducted with 20 individuals aged between 18 and 25. The intraoral pressures were measured through a system of cannulae connected to a digital pressure meter in the SPS during seven biofunctional phases. Descriptive statistics were used based on the mean and standard deviation. The data recorded pressure variations under physiological conditions, reaching 65 mbar as the intraoral peak in forced inspiration. In the swallowing phase, peaks reached -91.9 mbar. No pressure variations were recorded in terms of atmospheric changes with the mouth open and semi-open. The data obtained during the swallowing and forced inspiration phases indicated forced lingual activity. In the swallowing phase, the adequate position of the tongue creates negative intraoral pressure, which represents a fundamental mechanism for the physical stabilization of the soft palate. This information could contribute to subsequent research into the treatment of primary roncopathies.